2020
DOI: 10.1177/1120700020929314
|View full text |Cite
|
Sign up to set email alerts
|

Debridement, antibiotic pearls, and retention of the implant in the treatment of infected total hip arthroplasty

Abstract: In this article the authors describe a modified surgical technique developed to enhance the classical irrigation and debridement procedure to improve the possibilities of retaining a total hip arthroplasty (THA) undergoing acute periprosthetic joint infection (PJI). This technique, debridement antibiotic pearls and retention of the implant (DAPRI), aims to remove the intra-articular biofilm allowing a higher and prolonged local antibiotic concentration by using calcium sulphate antibiotic-added beads. The comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…This technique aims to remove the intra-articular biofilm by the combination of a tumor-like debridement of peri-prosthetic tissues, and argon beam application plus chlorhexidine gluconate brushing on the implant surfaces. This, combined with a higher and prolonged local antibiotic concentration by using calcium sulphate antibiotic-added beads, might enhance the disruption of the infection with an 80% rate of success in two recent consecutive preliminary studies 11,12 , which is higher than that reported with DAIR 38 . At our Institute, patients were routinely treated with DAPRI if the infection occurred in the first 3 post-operative weeks or in the first seven days after late hematogenous PJI.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This technique aims to remove the intra-articular biofilm by the combination of a tumor-like debridement of peri-prosthetic tissues, and argon beam application plus chlorhexidine gluconate brushing on the implant surfaces. This, combined with a higher and prolonged local antibiotic concentration by using calcium sulphate antibiotic-added beads, might enhance the disruption of the infection with an 80% rate of success in two recent consecutive preliminary studies 11,12 , which is higher than that reported with DAIR 38 . At our Institute, patients were routinely treated with DAPRI if the infection occurred in the first 3 post-operative weeks or in the first seven days after late hematogenous PJI.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, in case of suspected early post-operative infections, different cut-off values have been proposed for serum C-reactive protein (CRP), D-dimer and erythrocyte sedimentation rate (ESR), while synovial white blood cell count (WBC) and leukocyte esterase strip test are not recommended during the first six post-operative weeks 9,10 . A novel and promising strategy to treat acute cases of PJIs was recently proposed, which consists in the combination of debridement, antibiotic pearls, and retention of the implant (DAPRI) 11,12 . DAPRI allows to remove only the polyethylene or modular component of the prosthesis, reducing the time of the revision surgery and the impact on patient recovery.…”
Section: Introductionmentioning
confidence: 99%
“…There is, on the other hand, literature regarding the efficacy of calcium sulphate antibiotic-loaded beads used as a local delivery system, which do not act as a coating, but are, however, capable of a longer-lasting targeted local antibiotic release [ 22 ]. This carrier was also tested in the DAIR strategy, modified in “debridement, antibiotic pearls, and retention of the implant, DAPRI”, where the use of the beads is associated with a debridement strategy associated with the use of an argon beam for the dislodgment of the biofilm from the implant in 10 patients, with promising results [ 26 ].…”
Section: Periprosthetic Joint Infectionsmentioning
confidence: 99%
“…Contrariwise, up to a 90% PJI success rate has been reported in the literature with similar functional outcomes to uninfected prosthesis [ 1 , 14 16 ]. The reported success rate slightly varies depending on the procedure [ 17 19 ]. All those studies follow a thorough work-up, diagnostic criteria and treatment for PJI with better outcomes when the patients are treated by specialists in PJI [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%